Universe 2.0: Higgs quantum gravity - Böhm-Mäder, Johannes (Frontiers in Physics, 2026)
Since decades quantum gravity tries to close the gap to general relativity, but all attempts remain pure theory without empirical test. The present study now extends loop quantum gravity to a verified theory that determines how matter causes the space-time curvature. A recap of the ‘problem of time in quantum gravity’ reveals that quantum theory on principle cannot quantize time. Hence, we quantize time on a meta-level. The network links thus oscillate at the Planck frequency as an SU(2) gauge field. They carry a Planck energy each, which due to background independence is not directly effective. The Higgs field propagates in the space-time lattice as a lower frequency SU(2) fluctuation mode. A modified Higgs mechanism transfers energy from the space-time network to the massive particles, modifying the local space-time quanta. Linear combination of space-time quanta yields the space-time curvature due to macroscopic masses, in rotational symmetry the Schwarzschild or Kerr metric. Instead of Einstein’s field equations, Higgs quantum gravity reproduces the key solutions for static or stationary mass configurations. Yet, the empirical evidence for general relativity applies. Higgs quantum gravity represents the first experimentally verified quantum gravity, and the first theory predicting the space-time curvature by mass generation from the space-time structure.